Phenylpropiolic Acid Isolated in Cryogenic Nitrogen and Xenon Matrices: NIR and UV-Induced Study - Lopes S.; Nikitin T.; FAUSTO, RUI (AIP Publishing, 2023)
Phenylpropiolic acid (C6H5C≡CCOOH, PPA) isolated in nitrogen and xenon cryogenic matrices was studied by infrared spectroscopy. The experimental studies were complemented by a series of quantum chemical calculations carried out at the density functional theory (B3LYP) and MP2 levels of theory (with different basis sets). The calculations predicted the existence of two planar PPA conformers, differing in the arrangement of the carboxylic group. The higher-energy trans-PPA conformer has a negligible population in the gas phase at room temperature and was prepared in situ in the N2 cryomatrix through vibrationally-induced rotamerization of the lower-energy cis-PPA conformer, achieved using selective narrowband infrared excitation of the OH stretching coordinate of the latter species. Broadband UV (λ > 235 nm) irradiation of matrix-isolated cis-PPA was also undertaken, leading to the observation of cis-PPA → trans-PPA isomerization. No other UV-induced photoreactions were observed. The in situ generated trans-PPA conformer was found to decay back to cis-PPA in the dark by tunneling, and its lifetimes under different experimental conditions were determined. The assignment of the infrared spectra of both conformers is presented, considerably extending the vibrational information available on this molecule.